(untitled) (Annals of Medical Research, 2023)
Aim: Cesarean section rates have increased, and although various measures such as antenatal education programs have been introduced to correct this, these could not be performed face-to-face due to the COVID-19 pandemic and were largely carried out online. The aim of this study was to find out what effect traditional education during pregnancy and its online replacement have on the rate of cesarean births and how the pregnancy turns out in unusual situations. Materials and Methods: The research was designed as a retrospective cross-sectional study. Fifty women undergoing childbirth in our hospital who received online antenatal education (Group 1), 101 women who received classic education (Group 2), and 77 women receiving no education (Group 3) took part in the study. Patient data were retrieved from the hospital information system and patient records. Results: This study involved 228 pregnant women. Fifty pregnant women (22%) receiving antenatal online education were assigned to Group 1, 101 women (44%) receiving classic face-to-face education to Group 2, and 77 women (34%) receiving no education to Group 3. Forty percent of Group 1, given online education, and 62.4% of Group 2, given classic education, were able to give birth via the normal vaginal route, and the difference was statistically significant (0.001). Cesarean delivery rates were significantly higher in Group 1 (60%) than in Group 2 (37.6%) (0.001). Statistically similar results were determined in all three groups in terms of birth weight, birth length, and low birth weight. No significant difference was also observed between the three groups in terms of premature birth (37 weeks) (p = 0.67). Conclusion: Online antenatal education does not reduce cesarean delivery rates compared to classic education. However, neonatal outcomes are similar.